Particle swarm optimization for solving DNA sequence design problem - Noor Khafifah Khalid, 1984-; Zuwairie Ibrahim, supervisor; Fakulti Kejuruteraan Elektrik (2010)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2010